Pedagogical Competence of the High School Teacher - Fakhrutdinova, Anastasiya Viktorovna; Ziganshina, Mayya Rashidovna; Mendelson, Veronika Alexandrovna; Chumarova, Lyubov Grigorevna (International journal of higher education, 2020)
The need conditions the relevance of the article for the formation of higher education teachers' pedagogical competence as the optimal system and purposeful work in this direction has not yet been formed. The goal of the article lies in the analysis of the study of the theoretical aspects of higher education teachers' pedagogical competence and identifying the main types of professional competence. The leading approach to the study of this problem for the authors was their understanding of the concept of "competence", the distinction between the concepts of "qualification" and "competence", as well as an understanding of the essence of higher school teacher's pedagogical competence. The article presents a scheme of competencies of a higher school teacher, a distinction between key, subject and professional competencies. Taking into account the results of this study, it is possible to identify several scientific problems and promising areas that require further consideration: in particular, the development of new training programs for teachers of higher education institutions.